Production, employment, and income effects of commercialization of agriculture - von Braun, Joachim (International Food Policy Research Institute, 1994)
The three chapters in Part III report synthesis is findings from the microlevel IFPRI research in The Gambia, Guatemala, Kenya, the Philippines, and Rwanda, as well as from the other case studies presented in Part V. Any attempt to synthesize and generalize on the basis of the detailed case studies runs the risk of excessively extrapolating from special circumstances and of losing insights gained from these case studies, whose strengths are the detailed assessments of the commercialization-production-income-consumption-nutrition chain and the important feedbacks from these elements. This chapter, on the first elements of the commercialization chain, is therefore to be seen in the context of the following two chapters, and all the three synthesis chapters together are to be seen in the context of the rich insights from the individual studies discussed later.